TRAINING TO DEVELOPMENT OF PUPILS COGNITIVE ACTIVITY BY MEANS OF VIRTUAL PHYSICAL EXPERIMENT - V. Sharko (Kherson State University, 2013)
The article deals with theoretical content of teacher training the formation and development of pupils cognitive activity. The impact of virtual physical experiments on the course of these is determined, here is processes, recommendations on the design of the learning process, which on the development of pupils cognitive activity.